An anti-fibrosis pro-repair abdominal wall repair patch and a preparation method and application thereof

CN122745355APending Publication Date: 2026-09-15SOUTHEAST UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610583226.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-04-29
Publication Date
2026-09-15

Smart Images

  • Figure CN122745355A_ABST
    Figure CN122745355A_ABST
Patent Text Reader

Abstract

The application discloses an anti-fibrosis and pro-repair abdominal wall repair patch as well as a preparation method and application thereof. In view of the problem that the existing polylactic acid-glycolic acid copolymer patch is degraded to cause local acidification, induce inflammation and pathological fibrosis, the patch is prepared by adopting a four-arm structure polylactic acid-glycolic acid copolymer and a strontium-doped bioactive glass to optimize the degradation behavior, and a fused deposition forming process is adopted to construct a multi-level three-dimensional printing structure. The patch is a three-dimensional porous structure, has regular macropores with a pore size of 1-3 mm, and has a tensile modulus of 5-10 Mpa. The patch can continuously release alkaline bioactive ions during in-vivo degradation, actively neutralize acidic by-products, and maintain the microenvironment stability of the implantation area, so as to induce the M2 polarization of macrophages, promote the adhesion of fibroblasts and the secretion of ordered matrix, and can be used for preparing an abdominal wall defect repair material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to an anti-fibrotic and repair-promoting abdominal wall repair patch, its preparation method, and its application, belonging to the field of biomedical materials technology. Background Technology

[0002] Abdominal wall defects are typically caused by factors such as incisional hernias, trauma, infection, or congenital malformations. They not only disrupt the mechanical integrity and physiological function of the abdominal wall but can also lead to serious clinical complications such as intestinal incarceration and strangulation. Currently, tension-free repair surgery using synthetic mesh is the gold standard for treating abdominal wall defects. However, existing commercially available mesh materials primarily provide passive physical support and lack the biological functions to actively regulate the local microenvironment or guide orderly tissue regeneration. This significantly limits the therapeutic efficacy of functional abdominal wall reconstruction.

[0003] Polylactic-co-glycolic acid copolymer (PLGA) is a biodegradable synthetic polymer approved by the U.S. Food and Drug Administration (FDA). Due to its good biocompatibility, tunable degradation rate, and excellent processing properties, it has been widely used in tissue engineering and regenerative medicine. However, during in vivo hydrolysis, PLGA continuously releases acidic oligomers such as lactic acid and glycolic acid, leading to a significant decrease in the local pH value at the implantation site. This acidic microenvironment disrupts immune homeostasis, induces persistent inflammatory responses, and ultimately results in pathological fibrosis in the repaired area. Excessive fibrosis in abdominal wall defect repair not only significantly reduces the elastic modulus and mechanical compliance of regenerated tissue, weakening the physiological function of the abdominal wall, but also increases the risk of patch displacement, contracture, and abdominal wall dysfunction, severely affecting long-term repair outcomes.

[0004] Current anti-fibrosis strategies primarily rely on molecular drug intervention to reduce abnormal collagen deposition. However, these strategies often act on downstream effects of the fibrosis pathway, potentially interfering with normal tissue homeostasis and remodeling processes, leading to delayed repair, ectopic calcification, and other adverse consequences. In contrast, targeting upstream regulatory factors of fibrosis—especially the local inflammatory response triggered by the physicochemical properties of the implant material itself—shows promise for a more physiologically aligned treatment paradigm. Studies have shown that the physicochemical properties of implant materials, such as surface characteristics, degradation behavior, and mechanical properties, directly influence the local immune microenvironment, thereby regulating macrophage polarization and subsequent tissue remodeling outcomes. Therefore, precisely controlling the degradation behavior of PLGA-based patch materials to intervene in the fibrosis process from the upstream stage is an important research direction for improving the abdominal wall repair effect of PLGA patches.

[0005] In conclusion, the development of a novel composite patch capable of actively regulating the degradation microenvironment, effectively inhibiting fibrosis, and promoting functional regeneration of abdominal wall tissue is of great significance and urgent need for improving the quality of clinical repair of abdominal wall defects. Summary of the Invention

[0006] The purpose of this invention is to overcome the technical defects of existing polylactic acid-glycolic acid copolymer (PLGA) based abdominal wall repair patches, which release acidic byproducts during in vivo degradation, induce local chronic inflammation and pathological fibrosis, and provide an anti-fibrotic and repair-promoting abdominal wall repair patch that can regulate the local immune microenvironment, promote functional regeneration of abdominal wall tissue and inhibit fibrosis formation.

[0007] A second objective of this invention is to provide a method for preparing the aforementioned anti-fibrotic and repair-promoting abdominal wall repair patch.

[0008] A third objective of this invention is to provide the application of the aforementioned anti-fibrotic and repair-promoting abdominal wall repair patch in the repair of abdominal wall defects.

[0009] The above-mentioned objective of this invention is achieved through the following technical solution:

[0010] An anti-fibrotic and repair-promoting abdominal wall repair patch is prepared by fused deposition modeling using four-arm polylactic acid-glycolic acid copolymer (4a-PLGA), strontium-doped bioactive glass (Sr-BG), and polycaprolactone (PCL), and has a three-dimensional porous structure.

[0011] This invention employs a star-shaped topology four-armed PLGA (4a-PLGA) as the substrate for the patch. Compared to linear PLGA, the branched structure of 4a-PLGA imparts a higher molecular weight and lower molecular chain flexibility, significantly slowing down the hydrolysis rate. This can delay the concentrated release rate of acidic degradation products from the intrinsic material properties, reducing the risk of localized acidification. Simultaneously, 4a-PLGA has a higher glass transition temperature (approximately 48°C) and thermal decomposition temperature (approximately 275°C), which is beneficial for thermal stability during fused deposition modeling.

[0012] Strontium-doped bioactive glass (Sr-BG), as the core functional filler, is prepared via the sol-gel method and exhibits a uniform spherical particle morphology. Sr-BG can slowly and continuously release Si into physiological environments. 4Basic bioactive ions such as ⁺, Ca²⁺, and Sr²⁺ actively neutralize the acidic oligomers released during the degradation of 4a-PLGA, maintaining pH stability in the implantation area and eliminating chronic inflammation caused by the local acidic microenvironment. More importantly, the Sr²⁺ and other bioactive ions released by Sr-BG have a clear immunomodulatory function, effectively inhibiting the polarization of macrophages to the pro-inflammatory M1 phenotype induced by PLGA degradation products, while promoting the polarization of macrophages to the anti-inflammatory and pro-repair M2 phenotype. M2 macrophages, by secreting anti-inflammatory cytokines and regenerative growth factors, create a favorable local immune microenvironment for the functional regeneration of abdominal wall tissue, blocking pathological scar formation from the upstream stage of the fibrosis cascade.

[0013] Polycaprolactone (PCL) is used as an auxiliary component. Its good flexibility and printability improve the melt processing performance of the 4a-PLGA / Sr-BG composite system, ensuring the continuity of the filament and the forming accuracy during the fused deposition modeling process.

[0014] This invention utilizes fused deposition modeling (FDM) technology to fabricate the aforementioned material into a three-dimensional patch with a regular diamond-shaped macroporous structure and a pore size of 1–3 mm. This structure not only provides mechanical support that matches the abdominal wall tissue, with a tensile modulus of 5–10 MPa, effectively preventing hernia recurrence due to patch mechanical failure before the host tissue is fully regenerated, but also provides ample three-dimensional space for angiogenesis, cell migration, and nutrient exchange, promoting the integrated ingrowth of host tissue into the patch.

[0015] In summary, the core innovation of this invention lies in the synergistic effect of 4a-PLGA degradation regulation and Sr-BG ion release: on the one hand, the star-shaped topology of 4a-PLGA slows down the release rate of acidic degradation products, providing a time window for the neutralization effect of Sr-BG's alkaline ions; on the other hand, the alkaline ions continuously released by Sr-BG not only neutralize the acidic microenvironment and eliminate upstream stimulating factors that trigger chronic inflammation and fibrosis, but also actively regulate the polarization direction of macrophages with the released Sr²⁺, shifting the local immune state from pro-inflammatory and pro-fibrotic to anti-inflammatory and pro-regenerative. This synergistic mechanism enables the patch of this invention to achieve a unified effect of tissue regeneration and anti-fibrosis in vivo, overcoming the contradiction of traditional PLGA patches that promote fibrosis and inhibit regeneration.

[0016] Furthermore, the molecular weight of the 4a-PLGA is 30~60 kDa, preferably 40~50 kDa.

[0017] Furthermore, the SrO content in the strontium-doped bioactive glass is 5%~15%; preferably, the composition of the strontium-doped bioactive glass is SiO2:CaO:SrO = (70~80):(10~20):(5~15).

[0018] Furthermore, the average particle size of the strontium-doped bioactive glass is 100~300 nm, preferably 150~200 nm.

[0019] Furthermore, the tensile modulus of the patch is 5~10 MPa, preferably 6~8 MPa.

[0020] Furthermore, after the patch is degraded in PBS buffer for 56 days, the pH value of the degradation medium is maintained above 6.8, preferably within the range of 7.0 to 7.5.

[0021] Furthermore, the patch can induce macrophages to polarize to the M2 phenotype under in vitro culture conditions and promote fibroblast adhesion, spreading and collagen secretion.

[0022] Furthermore, the synthesis method of the 4a-PLGA (Jidong Dai, Min Liang, Zhigang Zhang, Katrien V. Bernaerts, Tianzhu Zhang, Synthesis and crystallization behavior of poly (lactide-co-glycolide). Polymer, 2021, 235, 124302.) includes the following steps:

[0023] S1. Place L-lactic acid, glycolide, and pentaerythritol in a round-bottom flask and mix thoroughly;

[0024] S2. Dissolve stannous octoate in dichloromethane to prepare a catalyst solution, and add it to the round-bottom flask mentioned above;

[0025] S3. The reaction mixture is treated under vacuum at 60°C for 30 minutes to remove moisture and dissolved oxygen;

[0026] S4. Seal the round-bottom flask, heat to 160°C, and continue the reaction for 8 hours under nitrogen protection;

[0027] S5. After the reaction is complete, cool the product to room temperature and dissolve it in dichloromethane;

[0028] S6. Slowly add the above solution dropwise into excess cold methanol, and stir vigorously to precipitate the product;

[0029] S7. The precipitate was collected by filtration, washed with cold methanol, and dried overnight in a vacuum drying oven at 30°C to obtain 4a-PLGA.

[0030] Preferably, in step S1, the mass ratio of L-lactic acid, glycolide, and pentaerythritol is 7.3:1.3:0.18.

[0031] Furthermore, the method for preparing the strontium-doped bioactive glass (Qianwen Yang, Anbei Chen, Xin Zhang, Zhaoying Wu, Chao Zhang, Functional poly(ether-ketone-ketone)composite scaffold with enhanced cell-material interaction, anti-inflammatory and osteogenesis for facilitating osteointegration and bone regeneration, Materials Today Bio, 2025, 31, 101533.) includes the following steps:

[0032] S1. Measure and mix anhydrous ethanol and ultrapure water, add ammonia to adjust the pH of the solution to alkaline, and stir well;

[0033] S2. Under stirring conditions, slowly add tetraethyl orthosilicate to the above solution and continue stirring for 30 minutes to ensure complete hydrolysis;

[0034] S3. Add calcium nitrate and strontium nitrate in sequence, and continue stirring for 2 hours to form a uniform sol;

[0035] S4. Arrange the sol at room temperature for 24 hours to form a wet gel;

[0036] S5. Place the wet gel in a 60°C oven and dry for 24 hours to obtain a dry gel;

[0037] S6. Grind the dry gel into powder, place it in a muffle furnace, heat it to 700°C at a heating rate of 5°C / min, and sinter it at that temperature for 3 hours;

[0038] S7. After naturally cooling to room temperature, wash the obtained powder alternately with anhydrous ethanol and deionized water, and collect it by centrifugation;

[0039] S8. Place the washed powder in a vacuum drying oven at 60°C and dry for 12 hours to obtain Sr-BG powder.

[0040] The present invention also provides a method for preparing the above-mentioned abdominal wall repair patch, comprising the following steps:

[0041] S1. Synthesis of 4a-PLGA;

[0042] S2. Preparation of strontium-doped bioactive glass via sol-gel method;

[0043] S3. Mix 4a-PLGA, Sr-BG and PCL uniformly in proportion, add the mixture to a micro twin-screw extruder for melt blending, with a screw speed of 30~50 rpm and a temperature of 160~180°C in each section; extrude the blended material through a micro single screw to produce a uniform printing filament with a diameter of 1.75 ± 0.05 mm, with an extrusion temperature of 170~190°C;

[0044] S4. The fused deposition modeling technique is used to prepare the printing filament into a patch with a pre-defined three-dimensional porous structure;

[0045] In step S4, an FDM printer is used, and the printing parameters are set as follows: nozzle temperature 200~220°C, platform temperature 35~45°C, printing speed 40~60 mm / s, filament width 0.3~0.5 mm, and filament spacing 1.5~2.5 mm. The printing program is started, and the patches are stacked layer by layer to form a patch with a regular large-pore structure. After printing, the patches are rinsed alternately with anhydrous ethanol and deionized water, dried, and then sealed and packaged for later use.

[0046] Preferably, in step S4, the printhead temperature is 210°C, the platform temperature is 40°C, the printing speed is 50 mm / s, the filament width is 0.4 mm, and the filament spacing is 2.0 mm.

[0047] The present invention also provides the application of any of the above-described abdominal wall repair patches in the preparation of abdominal wall defect repair materials.

[0048] The present invention also provides the application of any of the above-described abdominal wall repair patches in the preparation of repair materials that promote functional regeneration of abdominal wall tissue while inhibiting the formation of pathological fibrosis.

[0049] Compared with the prior art, the present invention has the following beneficial effects:

[0050] (1) The star-shaped topology of 4a-PLGA slows down the release rate of acidic degradation products, reducing the risk of local acidification from the perspective of the intrinsic properties of the material. The alkaline bioactive ions continuously released by Sr-BG actively neutralize the acidic microenvironment, maintain the pH stability of the implantation area, and eliminate upstream stimulating factors that cause chronic inflammation. The immunomodulatory function of Sr²⁺ ions released by Sr-BG induces M2 polarization of macrophages, regulates the immune microenvironment from the upstream link of the fibrosis process, and blocks the formation of pathological scars; the degradation regulation of 4a-PLGA and the release of Sr-BG ions form a synergistic effect, realizing the unity of tissue regeneration and anti-fibrosis.

[0051] (2) The three-dimensional porous structure constructed by fused deposition modeling technology provides mechanical support that matches the abdominal wall tissue, while promoting cell migration, angiogenesis and tissue integration ingrowth. The preparation process is mature and controllable, and has the potential for large-scale production and personalized customization.

[0052] (3) The star-shaped 4a-PLGA gives the patch better thermal stability and mechanical properties. The regular large-pore structure of 3D printing ensures long-term structural integrity after implantation and avoids early mechanical failure. At the same time, the degradation rate matches the tissue regeneration process, realizing a dynamic balance between regeneration replacement and material degradation.

[0053] (4) Good biocompatibility and safety: Hemolysis test and pathological analysis of major organs in vivo showed that the patch of the present invention has good blood compatibility and systemic safety, and no obvious toxic reaction. Attached Figure Description

[0054] Figure 1 The structure of 4a-PLGA is shown in the diagram; (a) shows the molecular weight determination by gel permeation chromatography (GPC), (b) shows the carbon nuclear magnetic resonance spectrum (¹³C-NMR), and (c) shows the hydrogen nuclear magnetic resonance spectrum (¹H-NMR).

[0055] Figure 2 The following are the processing performance characterization diagrams for 4a-PLGA; where (a) is the thermogravimetric analysis (TGA) curve and (b) is the differential scanning calorimetry (DSC) curve.

[0056] Figure 3 Characterization diagrams of strontium-doped bioactive glass (Sr-BG); where (a) is a transmission electron microscope (TEM) image, (b) is a dynamic light scattering (DLS) particle size distribution diagram, and (c) is an X-ray photoelectron spectroscopy (XPS) elemental analysis diagram.

[0057] Figure 4 The image shows the morphology of the printed patch; (a) is a digital photograph of the patch with a scale bar of 1 cm, and (b) is a scanning electron microscope (SEM) image and an energy dispersive spectroscopy (EDS-Mapping) elemental distribution map.

[0058] Figure 5 Stress-strain curves for the mechanical properties of different patches.

[0059] Figure 6 The image shows the contact angle test results for different patches.

[0060] Figure 7 A graph showing the blood compatibility evaluation of different patches.

[0061] Figure 8The graph shows the in vitro degradation characteristics of the patch; (a) is the curve of residual mass change during degradation, (b) is the curve of pH change of degradation solution, and (c) is the curve of Si, Ca and Sr ion release of 4aPB patch.

[0062] Figure 9 The images show the cell compatibility evaluation of different patches; (a) shows the live / dead fluorescence staining of NHDF cells on different patches, and (b) shows the proliferation detection results of CCK-8 cells.

[0063] Figure 10 The image shows the cytoskeleton staining of NHDF cells on different patches.

[0064] Figure 11 Images of NHDF cells stained with Sirius red on different patches.

[0065] Figure 12 The image shows flow cytometry analysis of RAW264.7 macrophages after different patch treatments, with M1 and M2 macrophages labeled with CD86 and CD206, respectively.

[0066] Figure 13 Images of hematoxylin-eosin (H&E) staining of major organs (heart, liver, spleen, lung, and kidney) in rats.

[0067] Figure 14 This image shows hematoxylin-eosin (H&E) staining of the abdominal wall defect 30 days after implantation.

[0068] Figure 15 Masson staining image of the abdominal wall defect 30 days after implantation.

[0069] Figure 16 This is a schematic diagram illustrating the preparation process of the present invention. Detailed Implementation

[0070] The present invention will be further described below with reference to the accompanying drawings and specific embodiments, but the embodiments do not limit the present invention in any way. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in this technical field.

[0071] Unless otherwise specified, all reagents and materials used in the following examples are commercially available.

[0072] Example 1: Synthesis of four-arm polylactic acid-glycolic acid copolymer (4a-PLGA)

[0073] The star-shaped 4a-PLGA was synthesized via ring-opening polymerization using pentaerythritol as an initiator and L-lactic acid and glycolide as monomers, catalyzed by stannous octoate. The specific procedures were as follows: 7.3 g of L-lactic acid (LA), 1.3 g of glycolide (GA), and 0.18 g of pentaerythritol were weighed and mixed thoroughly in a round-bottom flask. 80 μL of stannous octoate (Sn(Oct)₂) was dissolved in dichloromethane to prepare a catalyst solution with a concentration of 0.01 g / mL, which was then added to the round-bottom flask. The reaction mixture was treated under vacuum at 60 °C for 30 minutes to remove moisture and dissolved oxygen. The round-bottom flask was sealed and heated to 160 °C, and the reaction was continued for 8 hours under nitrogen protection. After the reaction was complete, the product was cooled to room temperature and dissolved in 20.0 mL of dichloromethane. The solution was slowly added dropwise to excess cold methanol, and the mixture was stirred vigorously to precipitate the product. The precipitate was collected by filtration, washed 2-3 times with cold methanol, and dried overnight in a vacuum drying oven at 30°C to obtain purified 4a-PLGA.

[0074] Gel permeation chromatography (GPC) determined the molecular weight of the obtained 4a-PLGA to be 43.8 kDa and the polydispersity index (PDI) to be 1.323. Carbon nuclear magnetic resonance (¹³C-NMR) and ¹H-NMR analyses confirmed the successful synthesis of the star-shaped PLGA (see [link to original text]). Figure 1 Thermogravimetric analysis (TGA) showed that 4a-PLGA remained thermally stable up to 275°C. Differential scanning calorimetry (DSC) measured a glass transition temperature (Tg) of approximately 48°C and a melting temperature (Tm) of approximately 66°C, both significantly lower than the thermal decomposition temperature, confirming its suitability for fused deposition modeling (see [link to relevant documentation]). Figure 2 ).

[0075] Example 2: Preparation of Strontium-doped bioactive glass (Sr-BG)

[0076] Strontium-doped bioactive glass was prepared using the sol-gel method, with the following specific steps: An appropriate amount of anhydrous ethanol and ultrapure water were mixed, and ammonia was added to adjust the pH to alkaline. The mixture was stirred until homogeneous. Under stirring conditions, tetraethyl orthosilicate (TEOS) was slowly added dropwise to the solution, and stirring was continued for 30 minutes to allow for complete hydrolysis of TEOS. Calcium nitrate (Ca(NO3)2) and strontium nitrate (Sr(NO3)2) were added sequentially, and stirring was continued for 2 hours to form a homogeneous sol. The sol was aged at room temperature for 24 hours to form a wet gel. The wet gel was dried in a 60°C oven for 24 hours to obtain a dry gel. The dry gel was ground into powder and placed in a muffle furnace, heated to 700°C at a heating rate of 5°C / min, and sintered for 3 hours. After natural cooling to room temperature, the obtained powder was washed three times alternately with anhydrous ethanol and deionized water, and collected by centrifugation. The washed powder was dried in a 60°C vacuum drying oven for 12 hours to obtain Sr-BG powder.

[0077] Transmission electron microscopy (TEM) showed that Sr-BG particles were uniformly spherical, and dynamic light scattering (DLS) determined that their average particle size was approximately 160 nm (see [link to TEM]). Figure 3 (a and 3b). X-ray photoelectron spectroscopy (XPS) analysis showed characteristic peaks for Si 2s, Si 2p, Sr 3d, Ca 2p, and O 1s. Inductively coupled plasma atomic emission spectrometry (ICP-OES) determined its elemental composition to be SiO2:CaO:SrO = 76.58:13.25:10.17 (mass ratio) (see [reference]). Figure 3 c).

[0078] Example 3: Preparation of Composite Printing Filament

[0079] Weigh out 4a-PLGA prepared in Example 1, Sr-BG powder prepared in Example 2, and polycaprolactone (PCL, molecular weight 80 kDa) and mix them evenly according to a predetermined mass ratio. Add the mixture to a micro twin-screw extruder for melt blending at a screw speed of 30-50 rpm and a temperature of 160-180℃ for each section. Extrude the blended material through a micro single-screw extruder to form uniform printing filaments with a diameter of 1.75 ± 0.05 mm at an extrusion temperature of 170-190℃, with the traction speed matched to the extrusion speed. Collect the resulting filaments by winding and placing them in a dryer for later use.

[0080] The following control filaments were prepared using the same method: LP filament: linear PLGA (L-PLGA, molecular weight 13.6 kDa, synthesized by the same ring-opening polymerization method but without pentaerythritol) was used instead of 4a-PLGA and mixed with PCL without adding Sr-BG; 4aP filament: 4a-PLGA was mixed with PCL without adding Sr-BG.

[0081] Example 4: Fabrication of composite patches by fused deposition modeling

[0082] The printing filaments obtained in Example 3 were loaded into the feeding system of a fused deposition modeling (FDM) printer (MAGIC-HT-RRO). The printing parameters were set as follows: nozzle temperature 210°C, printing platform temperature 40°C, printing speed 50 mm / s, layer height 0.2 mm, filament width 0.4 mm, filament spacing 2.0 mm, and a diamond-shaped infill pattern (alternating grid angles ±45°). The printing program was started, and layers were deposited one by one to form a three-dimensional patch with a regular large-pore structure. The number of printing layers was 10-15, with a total thickness of approximately 2.0-3.0 mm. After printing, the patch was removed from the platform, rinsed three times alternately with anhydrous ethanol and deionized water, dried in a 30°C vacuum drying oven for 4 hours, and then sealed in packaging for later use.

[0083] The resulting patches were named as follows: LP patch (control): prepared by printing with LP filament; 4aP patch (control): prepared by printing with 4aP filament; 4aPB patch (Example 4): prepared by printing with 4a-PLGA / PCL / Sr-BG filament.

[0084] Example 5: Physicochemical property characterization of the patch

[0085] 5.1 Morphological and structural observation

[0086] After printing, the patch structure is clear and complete, exhibiting a uniform diamond-shaped large-hole structure (see...). Figure 4 a) Scanning electron microscopy (SEM) revealed that all patches exhibited a distinct 3D-printed macroporous structure, with the 4aPB patch showing a rougher microsurface and visible uniformly distributed spherical particles (Sr-BG particles). Energy dispersive spectroscopy (EDS) mapping showed a uniform distribution of C in the LP, 4aP, and 4aPB patches, while a uniform distribution of Si was observed only in the 4aPB patch, confirming the successful incorporation of Sr-BG into the patch matrix (see [link to EEM]). Figure 4 b).

[0087] 5.2 Mechanical property testing

[0088] The patch was cut into 10 mm wide strips, and its mechanical properties were tested using a universal testing machine at a tensile rate of 5 mm / min. Stress-strain curves (see...) Figure 5The tensile moduli of the LP, 4aP, and 4aPB patches were 2.49 MPa, 6.03 MPa, and 7.88 MPa, respectively. The results indicate that the 4aPB patch possesses the highest mechanical strength, which is attributed to the hydrogen bond interaction between the Sr-BG particles and the hydroxyl groups in the 4a-PLGA molecular chain, enhancing the mechanical properties of the composite system. This mechanical strength can effectively reduce the risk of abdominal hernia recurrence due to patch failure before complete host tissue regeneration.

[0089] 5.3 Surface hydrophilicity test

[0090] The water contact angles of each group of patches were measured using a contact angle meter. The results showed that the contact angles of the LP, 4aP, and 4aPB patches were 95.63°±2.33°, 100.97°±5.96°, and 69.79°±5.59°, respectively (see [link to relevant documentation]). Figure 6 The significantly reduced contact angle of the 4aPB patch indicates that the introduction of Sr-BG effectively enhances the hydrophilicity of the patch surface, which is beneficial for the deposition of cell adhesion-related proteins and the spreading of cells on the material surface.

[0091] 5.4 Blood compatibility evaluation

[0092] Each patch group was incubated with 2% erythrocyte suspension at 37°C for 1 hour. After centrifugation, the absorbance of the supernatant at 540 nm was measured, and the hemolysis rate was calculated. Results (see...) Figure 7 The results showed that the hemolysis rate of each patch group was less than 5%, indicating that the material has good blood compatibility and causes little damage to red blood cells.

[0093] 5.5 In vitro degradation behavior and pH change monitoring

[0094] Each patch group was immersed in PBS buffer at 37°C. Samples were taken periodically, weighed, and the PBS was replaced with fresh PBS (for quality change monitoring) or not replaced (for pH monitoring). Degradation curves (see appendix). Figure 8 a) The data shows that the LP patch exhibited the fastest degradation rate, with a residual mass of approximately 91.52% after 56 days; the 4aP and 4aPB patches showed similar degradation rates, with residual masses of approximately 96.19% and 95.54%, respectively, after 56 days. The pH change curve of the degradation solution is shown in the appendix. Figure 8 (b) Three different patterns were observed: the pH of the LP group continuously decreased, reaching approximately 3.25 at day 56; the pH of the 4aP group decreased slowly, reaching approximately 5.28 at day 56; and the pH of the 4aPB group rose slightly to approximately 7.43 in the first 3 days, then decreased at a very slow rate, remaining at 7.12 at day 56. These results indicate that the alkaline ions released by Sr-BG effectively neutralized the acidic byproducts of PLGA degradation, maintaining local pH stability.

[0095] 5.6 Ion Release Behavior Test

[0096] The 4aPB patch was immersed in PBS at 37°C, and samples were taken at different time points. The concentrations of Si, Ca, and Sr ions in the release medium were determined by ICP-OES. Results (see...) Figure 8 c) shows that Si, Ca, and Sr ions all exhibited continuous release behavior, with cumulative release amounts of 31.35 mg / L, 41.67 mg / L, and 7.21 mg / L over 56 days, respectively.

[0097] Example 6: In vitro cell experiments

[0098] 6.1 Evaluation of cell compatibility and proliferation

[0099] Normal human diploid fibroblasts (NHDF) were seeded onto the surface of patches in each group, and live / dead fluorescence staining (FDA / PI) was performed after 1, 3, and 5 days of culture. The results showed that the number of NHDF cells on the surface of each group of patches increased significantly with prolonged culture time, indicating good cell compatibility. At 5 days of culture, the fluorescent area on the surface of the 4aPB patch was significantly higher than that of the LP and 4aP groups (see [link to relevant documentation]). Figure 9 a). CCK-8 quantitative detection results (see...) Figure 9 b) Consistent with the live / dead staining results, the 4aPB group had the highest cell count after 5 days of culture.

[0100] 6.2 Cell adhesion and morphological observation

[0101] After NHDF cells were seeded onto the surfaces of each patch and cultured for 3 days, fluorescent staining of the cytoskeleton (phalloidin) and nucleus (DAPI) was performed. Observation was then performed using laser confocal microscopy (see [link to documentation]). Figure 10 The results showed that cells on the LP and 4aP patches exhibited a slightly stretched spherical morphology, while cells on the 4aPB patch surface were more spread out, exhibiting a polygonal spread, and the average spread area was significantly larger than the other two groups. These results indicate that the introduction of Sr-BG enhances the hydrophilicity of the patch surface, which is beneficial for fibroblast adhesion and spread.

[0102] 6.3 Evaluation of Collagen Secretion

[0103] Sirius red staining was used to assess total collagen secretion by NHDF cells on different patches. Staining results after 3 days of culture (see [link to staining results]). Figure 11 The results showed that LP and 4aP patches significantly inhibited collagen expression, while the 4aPB patch group had the largest staining area, indicating the highest collagen secretion. This confirms that the 4aPB patch not only does not inhibit normal repair cell function, but also promotes the physiological secretion of the extracellular matrix.

[0104] 6.4 Macrophage Polarization Analysis

[0105] After co-culturing RAW264.7 mouse mononuclear macrophages with patches from various groups for 3 days, the expression of the M1 marker CD86 and the M2 marker CD206 was detected by flow cytometry. Results (see...) Figure 12 The results showed that the proportions of M1 macrophages in the LP group and the 4aP group were approximately 60.3% and 56.1%, respectively, while the proportion of M2 macrophages was less than 1% in both groups. In contrast, no large number of M1 macrophages were observed in the 4aPB group, and the proportion of M2 macrophages was approximately 9.9%. These results indicate that the bioactive ions released by Sr-BG effectively inhibited the M1 pro-inflammatory polarization of macrophages induced by PLGA degradation products and promoted macrophage polarization towards the M2 anti-inflammatory / pro-repair phenotype.

[0106] Example 7: Rat Abdominal Wall Defect Repair Experiment

[0107] 7.1 Animal Model Establishment and Patch Implantation

[0108] Male SD rats (8-12 weeks old, weighing approximately 300 g) were selected. After anesthesia, the abdomen was cleaned and incised along the lateral edge of the abdominal cavity to expose the abdominal muscles. A 1.0 cm × 0.5 cm full-thickness defect was created on the abdominal wall, and LP, 4aP, and 4aPB patches were sutured and fixed to the defect. All animal experiments were approved by the Institutional Animal Care and Use Committee of Southeast University (SEU-IACUC-20250418002).

[0109] 7.2 In vivo biosafety evaluation

[0110] Two weeks after implantation, major organs (heart, liver, spleen, lung, and kidney) of rats were harvested for H&E staining and histopathological analysis. Results (see...) Figure 13 The results showed that no obvious lesions or inflammatory cell infiltration were observed in any of the organs, indicating that all patches had good biocompatibility in vivo and no systemic toxicity.

[0111] 7.3 Evaluation of the repair effect of abdominal wall defects

[0112] Thirty days after implantation, tissue samples were taken from the defect site for H&E staining and Masson staining histological analysis.

[0113] H&E staining results (see) Figure 14The results showed that the LP group had poor healing, with regenerated tissue thickness only 38.49% ± 9.30% of the normal abdominal wall thickness, and significant inflammatory cell infiltration was still visible, indicating persistent chronic inflammation. The 4aP group had a regenerated tissue thickness of 52.04% ± 6.96% and fewer inflammatory cells. The 4aPB group had a regenerated tissue thickness of 83.01% ± 3.91%, close to the normal abdominal wall thickness, and almost no significant inflammatory cells were observed. The 3D-printed macroporous structure of the patches in all groups remained relatively intact, avoiding hernia recurrence due to rapid degradation.

[0114] Masson staining results (see...) Figure 15 The results showed that in the LP group, collagen deposition increased but was unevenly distributed, with collagen fibers curled and exhibiting obvious scar tissue characteristics. No muscle regeneration was observed, and a clear boundary existed between fibrotic repair and regenerated tissue. In the 4aP group, collagen arrangement was more orderly, and the fibrotic boundary was relatively blurred, but almost no muscle regeneration was observed. In the 4aPB group, significant muscle regeneration was observed, with orderly and uniform collagen distribution and only a small amount of scar-like tissue, indicating that fibrotic repair was significantly inhibited. Notably, muscle regeneration occurred first on the side closer to the scaffold, which may be related to the concentration gradient of active ions released within the scaffold.

[0115] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.

Claims

1. An anti-fibrotic pro -remodelling abdominal wall repair patch, characterized in that, It is constructed by fused deposition modeling technology using four-arm polylactic acid-glycolic acid copolymer, strontium-doped bioactive glass and polycaprolactone. The resulting patch has a three-dimensional porous structure with regular macropores of 1~3 mm in diameter and a tensile modulus of 5~10 MPa. The star-shaped topology of 4a-PLGA regulates the release rate of acidic degradation products, while Sr-BG continuously releases alkaline bioactive ions to actively neutralize the acidic microenvironment. The two work synergistically to achieve a combination of tissue regeneration and anti-fibrosis in vivo.

2. An anti-fibrotic pro -remodelling abdominal wall repair patch according to claim 1, characterised in that, The molecular weight of the 4a-PLGA is 30~60 kDa, preferably 40~50 kDa.

3. The anti-fibrotic pro -remodeling abdominal wall repair patch of claim 1, wherein, The SrO content in the strontium-doped bioactive glass is 5%~15%; the composition of the strontium-doped bioactive glass is SiO2:CaO:SrO = (70~80):(10~20):(5~15); the average particle size of the strontium-doped bioactive glass is 100~300 nm, preferably 150~200 nm.

4. A method for preparing an anti-fibrotic and repair-promoting abdominal wall repair patch as described in any one of claims 1 to 3, characterized in that, Includes the following steps: Step (1) Synthesizing 4a-PLGA by ring-opening polymerization: Using pentaerythritol as an initiator, L-lactic acid and glycolide as monomers, it is prepared by ring-opening polymerization under the catalysis of stannous octoate. Step (2): Strontium-doped bioactive glass is prepared by sol-gel method; Step (3): Mix 4a-PLGA, Sr-BG and PCL in a uniform ratio and melt-extrude them to make printing filaments; Step (4): The printed filament is prepared into a patch with a preset three-dimensional porous structure using fused deposition modeling technology.

5. The method for preparing an anti-fibrotic and repair-promoting abdominal wall repair patch according to claim 4, characterized in that, The process parameters for fused deposition modeling in step (4) are: nozzle temperature 200~220℃, platform temperature 35~45℃, printing speed 40~60 mm / s, filament width 0.3~0.5 mm, and filament spacing 1.5~2.5 mm.

6. The method for preparing an anti-fibrotic and repair-promoting abdominal wall repair patch according to claim 4, characterized in that, In step (3), the mixture is added to a micro twin-screw extruder for melt blending. The screw speed is 30~50 rpm and the temperature of each section is 160~180°C. The mixture is melt extruded to produce a uniform printing filament with a diameter of 1.75 ± 0.05 mm. The extrusion temperature is 170~190°C.

7. The use of an abdominal wall repair patch as described in any one of claims 1 to 4 in the preparation of abdominal wall defect repair materials.

8. The application according to claim 7, characterized in that, The abdominal wall defect repair material is used to promote functional regeneration of abdominal wall tissue while inhibiting the formation of pathological fibrosis.